Learning Environment and Academic Performance in Physical Therapist (Kinesiology) Students During Clinical Internship: An Assessment from the Student Perspective. - Tiemann-Hernández, Paula; Herrera-Lillo, Antonieta; Urrejola-Contreras, Gabriela P. (Spanish Journal of Medical Education, 2025)
Introduction: The clinical internship is a crucial final stage in health sciences training; however, it can present challenges linked to the Educational Environment (EE) that may impact academic performance. This study aimed to correlate the perception of the EE with the academic performance of Kinesiology students during their clinical internships. Methods: An observational, cross-sectional, correlational study was conducted with the entire cohort of fifth-year Kinesiology students (n=20) at the Universidad Viña del Mar, Chile. The perception of the EE was measured using the validated PHEEM questionnaire (assessing autonomy, teaching, and social support). Academic performance was evaluated through the grades obtained from solving authentic clinical cases in musculoskeletal, cardiorespiratory, and neurorehabilitation areas. Statistical analysis determined the correlation between both variables. Results: The global perception of the EE was positive (Total PHEEM score: 116.3/160). Academic performance was satisfactory and passing in all areas (Average grades: Musculoskeletal: 5.1, Cardiorespiratory: 5.5, Neurorehabilitation: 5.3). However, a weak and generally non-significant overall correlation was found between the PHEEM score and academic performance (r=0.3). A moderate correlation was identified only in the cardiorespiratory area (r=0.5). Discussion: Contrary to the initial hypothesis and much of international literature, a robust association between the perception of the EE and academic performance was not confirmed. The results suggest that performance during clinical internships is multifactorial and may be more strongly influenced by other variables not measured in this study, such as individual stress levels, resilience, or the quality of supervisory feedback. These findings highlight the need for a comprehensive approach to clinical training that considers these other determinants alongside the educational environment.